2018
DOI: 10.1007/s11060-018-2966-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glioma growth by a GOLPH3 siRNA-loaded cationic liposomes

Abstract: This study shows that GOLPH3 has great potential as a target for the gene therapy of glioma and is of great value in precise medical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Actually, in the last 2 years, some authors reported on this topic. Yuan and collaborators [73] targeted GOLPH3 through siRNA loaded on cationic liposomes, obtaining the inhibition of glioma growth in vivo, in a nude mouse model. A similar nanoparticle-mediated approach was used by Ye and co-workers, who co-delivered GOLPH3 siRNA and gefitinib (Ge, an anti-EGFR drug) in vitro (U87 and T98G glioma cell lines) and in vivo (BALB/c nude mice), obtaining growth inhibition and apoptosis induction [74].…”
Section: Golph3 Deregulation and Brain Tumorsmentioning
confidence: 99%
“…Actually, in the last 2 years, some authors reported on this topic. Yuan and collaborators [73] targeted GOLPH3 through siRNA loaded on cationic liposomes, obtaining the inhibition of glioma growth in vivo, in a nude mouse model. A similar nanoparticle-mediated approach was used by Ye and co-workers, who co-delivered GOLPH3 siRNA and gefitinib (Ge, an anti-EGFR drug) in vitro (U87 and T98G glioma cell lines) and in vivo (BALB/c nude mice), obtaining growth inhibition and apoptosis induction [74].…”
Section: Golph3 Deregulation and Brain Tumorsmentioning
confidence: 99%
“…In addition to chemotherapy, immunotherapies, such as CAR-T [ 68 , 69 , 70 , 71 ] and immune checkpoint inhibitors of cytotoxic T lymphocyte-associated protein 4 (CTLA-4), programmed cell death protein 1 (PD-1), and programmed cell death protein 1 ligand (PD-L1) [ 72 , 73 , 74 ], have been recently investigated for GBM treatment. Moreover, induced pluripotent stem cell-based regenerative medicine [ 75 ] and gene therapies (adenovirus, herpes simplex virus-1, retrovirus, shRNA, siRNA, non-viral vectors) have been developed and evaluated [ 76 , 77 , 78 , 79 ]. We will evaluate the combination of our mAb-EV-Ver-A and immunotherapy or gene therapy for GBM treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Conveniently, cationic liposomes are amenable to carrying both drugs and genes [30]. Angiopep-2-functionalized cationic liposomes were shown to effectively deliver siRNA against Golgi phosphoprotein 3 (GOLPH3) specifically to glioma and inhibit its growth in U87-GFP-Luci-bearing BALB/c mouse models [31].…”
Section: Angiopep-2-decorated Nanoparticlesmentioning
confidence: 99%